Customer selection criteria for islamic home financing in Johor / Murni Farhana Talib - Talib, Murni Farhana (2011)
Nowadays, financial institution plays a great role in providing home financing facility. Thus, the purpose of this project paper is to find out the choice criteria for Islamic home financing in Malaysian Islamic banks. The important part of this study considers establishing a specific rank of choice criteria for Islamic home financing and determines the most important factors that affects customer in considering Islamic home financing facility in Islamic banks. This study presents primary data collected by self-administered questionnaires involving a sample of 400 respondents in Johor state. All questionnaires were returned and analyzed using frequencies, reliability test, and regression analysis. The results suggest that “Shariah-compliant scheme” is the most important factors followed by reputation, service quality, and influence from others and lastly is convenience. While conducting this study, it also have several implications such as time constraint, financial constraints, lack of co-operation from respondents, questionnaire misinterpretation, and facing with respondents who have lack of knowledge. Based on the study done, its implications would primarily beneficial in Malaysia by offering an insight into choice criteria for Islamic home financing. This study provides new results about different kinds of customers’ types and their preferences with regards to Islamic home financing selection. As such, Islamic bank managers can learn and plan to offer attractive schemes for the Islamic home financing market that meet Malaysian bank customers’ needs. For the researcher, this study contributes to existing body of knowledge by providing an investigation of choice criteria in the Islamic home financing. Indeed, this study is considered an “eye-opener” for Islamic home financing choice criteria which has limited previous studies. Other than that, the recommendations also being voiced out for the purpose to assist future researcher to render benefits from it and make a better research in the future